Synthesis and exploration of configurational dynamics in equilibrating E/Z 2-aryliminothiazolidin-4-ones using NMR and estimation of thermodynamic parameters. (22nd February 2022) - Singh, Rahul; Kumar, Parvin; Sindhu, Jayant; Devi, Meena
Abstract : NMR based in-depth exploration of stereodynamic behavior in equilibrating E / Z 2-aryliminothiazolidin-4-ones and determination of kinetic and thermodynamic parameters. Abstract : In the present study, 2-aryliminothiazolidin-4-ones (3 and 5 ) were utilized as dynamic chemical systems, whose different states are modulated in a reversible fashion through specific chemical stimuli. The in-depth NMR investigation revealed that the magnitude of rotational energy barrier (Δ G ‡ ) is affected markedly by (1) the solvent polarity; (2) the electronic nature of the ring system present on the exocyclic CN bond and (3) the temperature of the system. The derivatives of 5-(3-arylallylidene)-2-(arylimino)thiazolidin-4-one exist in two isomeric forms at room temperature in DMSO- d 6 : (2 E, 5 Z, 7 E ) ⇆ (2 Z, 5 Z, 7 E ). The stereodynamics of the synthesized derivatives (5a–5t ) has been investigated using variable temperature dynamic 1 H-NMR (VT DNMR). The Δ G ‡ values (≈15 kcal mol −1 ) estimated for the dynamic process depict a significant barrier between two forms in solution at ambient temperature. To go a step further, line shape analysis was also performed to get a clear understanding of the equilibration mechanism.